24-Month Clinical, Immuno-Virological Outcomes, and HIV Status Disclosure in Adolescents Living With Perinatally-Acquired HIV in the IeDEA-COHADO Cohort in Togo and Côte d'Ivoire, 2015–2017 - Dassi Tchoupa Revegue, Marc Harris; Takassi, Unoo Elom; Tanoh Eboua, François; Desmonde, Sophie; Amoussou-Bouah, Ursula Belinda; Bakai, Tchaa Abalo; Jesson, Julie; Dahourou, Désiré Lucien; Malateste, Karen; Aka-Dago-Akribi, Hortense; Raynaud, Jean-Philippe; Arrivé, Elise; et al. (Frontiers in Pediatrics, 2021)
Background: Adolescents living with perinatally-acquired HIV (APHIV) face challenges including HIV-serostatus disclosure. We assessed their 24-month outcomes in relation to the disclosure of their own HIV-serostatus. Methods: Nested within the International epidemiologic Database to Evaluate AIDS pediatric West African prospective cohort (IeDEA pWADA), the COHADO cohort included antiretroviral (ART)-treated APHIV aged 10–19 years, enrolled in HIV-care before age 10 years, in Abidjan (Côte d’Ivoire) and Lomé (Togo) in 2015. We measured HIV-serostatus disclosure at baseline and after 24 months and, analyzed its association with a favorable combined 24-month outcome using logistic regression. The 24-month combined clinical-immuno-virological outcome was defined as unfavorable when either death, loss to follow-up, progression to WHO-AIDS stage, a decrease of CD4 count >10% compared to baseline, or a detectable viral load (VL>50copies/mL) occurred at 24 months. Results: Overall, 209 APHIV were included (51.6%=Abidjan, 54.5%=females). At inclusion, median CD4 cell count was 521/mm3 (IQR[281-757]); 29.6% had a VL measurement, of whom 3.2% were virologically suppressed. APHIV were younger in Lomé (median age: 12 years (interquartile range [IQR]:11-15) compared to Abidjan (14 years (IQR:12-15, p=0.01). Full HIV-disclosure increased from 41.6% at inclusion to 74.1% after 24 months. After 24 months of follow-up, 6 (2.9%) died, 8 (3.8%) were lost to follow-up, 4 (1.9%) were transferred out. Overall, 73.7% did not progress to WHO-AIDS stage, 62.7% had CD4 count above (± 10%) of the baseline value (48.6% in Abidjan versus 69.0% in Lomé, p<0.001). Among the 83.7% with VL measurement, 48.8% were virologically suppressed (Abidjan: 45.4%, Lomé: 52.5%, p<0.01). The 24-month combined outcome was favorable for 45% (29.6% in Abidjan and 61.4% in Lomé, p<0.01). Adjusted for baseline variables, the 24-month outcome was worse in Lomé in those who had been disclosed > 2 years compared to those not disclosed to (aOR=0.21, 95%CI [0.05-0.84], p=0.03). Conclusions: The frequency of HIV-disclosure improved over time and differed across countries but remained low among West-African APHIV. Overall, 24-month outcomes were poor. Disclosure before the study was a marker of poor 24-month outcome in Lomé. Context-specific responses are urgently needed to improve adolescent care and reach the UNAIDS 90% target of virological success.